A Historical Note on the Assimilation Rates of Foreign-Born Women in the U.S. - Harriet Duleep; Dan Dowhan; Xingfei Liu (Global Labor Organization (GLO), 2023)
Using historical, longitudinal data on individuals, we track the earnings of immigrant and U.S.-born women. Following individuals, instead of synthetic cohorts, avoids biases in earnings-growth estimates caused by compositional changes in the cohorts that are followed. The historical data contradict key predictions of the Family Investment Hypothesis, shed light on its genesis, and inform its further testing. Challenging the perception that the quality of U.S. immigrants fell after the 1965 Immigration and Nationality Act, immigrant women, as previously found for immigrant men, have high earnings growth.
Keywords: J15; J16; J24; J31; C1; 330; Immigrant earning growth; human capital investment; skill transferability; immigrant quality; sample restrictions; family investment model